(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda is a traditional herbal medicine system with a lengthy history and solid foundation in India. In both preventing and treating human illnesses, herbal plants are crucial. Traditional human medicine has been derived from plants since ancient times. Throughout history, plants have played a significant role in shaping human civilization. Yet, it is thought that plants are abundant in the phytochemical components necessary for their therapeutic benefits. It may be possible to create novel herbal medications by using medicinal plants. Today, the pharmacological properties of medicinal plants are seen to be a promising new class of drug or medication for the treatment of medical conditions. Rediscovered medicinal plants have piqued curiosity as a possible source of novel drugs in recent years. Thus, the current review’s goal is to comprehend our current understanding of medicinal plants as a potential source for herbal medications in the future.